Identification and functional characterization of protein kinase R (PKR) in amphibian Xenopus tropicalis. (April 2023) - Gan, Zhen; Xu, Xinlan; Tang, Shaoshuai; Wen, Qingqing; Jin, Yong; Lu, Yishan
Abstract: As one of interferon-induced serine/threonine kinases, the protein kinase R (PKR) plays vital roles in antiviral defense, and functional features of PKR remain largely unknown in amphibians, which suffer from ranaviral diseases in the last few decades. In this study, a PKR gene named Xt-PKR was characterized in the Western clawed frog ( Xenopus tropicalis ). Xt-PKR gene was widely expressed in different organs/tissues, and was rapidly induced by poly(I:C) in spleen, kidney, and liver. Intriguingly, Xt-PKR could be up-rugulated by the treatment of type I and type III interferons, and the transcript level of Xt-PKR induced by type I interferon was much higher than that of type III interferon. Moreover, overexpression of Xt-PKR can suppress the protein synthesis and ranavirus replication in vitro, and the residue lysine required for the translation inhibition activity in mammalian PKR is conserved in Xt-PKR. The present study represents the first characterization on the functions of amphibian PKR, and reveals considerable functional conservation of PKR in early tetrapods. Highlights: A PKR gene named Xt-PKR was identified and characterized in Xenopus tropicalis. Xt-PKR gene is rapidly up-regulated after poly(I:C) stimulation. The expression of Xt-PKR is induced by type I and type III IFNs in vivo. Xt-PKR has the activity to inhibit reporter protein translation in vitro. Xt-PKR is involved in the suppression of ranavirus replication in A6 cells.